Financial Cost-Benefit Analysis of Investment Possibilities in District Heating System on Wood Residues - Stošić, Ivan; Domazet, Ivana; Đuričin, Sonja; Beraha, Isidora (Industrija, 2017)
The purpose of this research is to provide feasibility analysis of a long-term sustainable development concept for district heating based on wood residues. In this paper, the experimental study has been conducted starting from the data collected by field researches in municipality of Trstenik ( town in Serbia with district heating system currently based on heavy fuel oil and lignite). Using the method of Financial Cost-Benefit Analysis, this study evaluates financial efficiency of investment in district heating plant based on wood residues and energy savings in district heating system. Findings show that such investment could be profitable from the financial point of view: Net Present Value of investment is positive, Financial Rate of Return is high (30.69%), and the pay-back period is relatively favourable (7 years). Moreover, the presented SWOT indicates that there are realistic prospects of implementation of district heating based on wood residues. However, this does not mean everything will go smoothly and easily, keeping in mind a number of challenges that each new concept of district heating contains immanently. Nevertheless, the results of this research could provide useful inputs for the decision makers when selecting appropriate models for improving performance of municipal district heating systems.
Keywords: Wood; Investment; District heating